2012
DOI: 10.1016/s0140-6736(11)61226-9
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab and bone-metastasis-free survival in men with castration-resistant prostate cancer: results of a phase 3, randomised, placebo-controlled trial

Abstract: Background Bone metastases are a major cause of morbidity and mortality in men with prostate cancer. Preclinical studies suggest that osteoclast inhibition may prevent bone metastases. This phase 3 study evaluated denosumab, a fully human anti-RANKL monoclonal antibody, to prevent bone metastasis or death from any cause in men with non-metastatic castration-resistant prostate cancer (CRPC). Methods Men with non-metastatic CRPC at high risk for bone metastasis (PSA ≥8.0 ng/mL and/or PSA doubling time ≤10.0 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
506
3
23

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 705 publications
(537 citation statements)
references
References 30 publications
5
506
3
23
Order By: Relevance
“…Nevertheless, no meaningful clinical extraskeletal effects have been reported after denosumab administration for osteoporosis, and the overall rate of infections, cancer, and patient mortality have been similar with denosumab use compared with placebo at doses used for the treatment of patients with osteoporosis [5,20]. High-dose denosumab therapy, similar to that used in patients with an unresectable giant cell tumor of bone, was recommended for prevention of skeletal-related events in patients with bone metastasis from a solid tumor [21]. In that study, it was difficult to assess long-term side effects related to denosumab therapy as patients had a limited life expectancy owing to the oncologic disease [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, no meaningful clinical extraskeletal effects have been reported after denosumab administration for osteoporosis, and the overall rate of infections, cancer, and patient mortality have been similar with denosumab use compared with placebo at doses used for the treatment of patients with osteoporosis [5,20]. High-dose denosumab therapy, similar to that used in patients with an unresectable giant cell tumor of bone, was recommended for prevention of skeletal-related events in patients with bone metastasis from a solid tumor [21]. In that study, it was difficult to assess long-term side effects related to denosumab therapy as patients had a limited life expectancy owing to the oncologic disease [21].…”
Section: Discussionmentioning
confidence: 99%
“…High-dose denosumab therapy, similar to that used in patients with an unresectable giant cell tumor of bone, was recommended for prevention of skeletal-related events in patients with bone metastasis from a solid tumor [21]. In that study, it was difficult to assess long-term side effects related to denosumab therapy as patients had a limited life expectancy owing to the oncologic disease [21].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies by the same author using independent data sets found similar conclusions. 67 More recently, denosumab was compared with ZA in patients with BM from several types of solid tumors and multiple myeloma; 1,68,69 in these studies, denosumab was more effective delaying time to first and subsequent SRE, which was correlated with a greater control of bone turnover marker levels (NTX-I and BALP). 1,68 Costa et al 12 further studied the role of bone markers in the diagnosis of disease progression.…”
Section: Prediction Of Patients' Outcomesmentioning
confidence: 99%
“…2,70 These phase 2 studies were crucial to select the treatment schedule of denosumab in the three pivotal phase 3 trials that led to the approval of this new BTA. 1,68,69 Despite the evidence that BTAs provide a significant clinical benefit for patients with BM, these drugs are also responsible Bone remodeling markers in bone metastatic disease A Ferreira et al for relevant adverse events, such as hypocalcemia or osteonecrosis of the jaw. 71 Moreover, the rate of adverse events associated with BP treatment increases with time, 71 and only limited evidence assessed long-term use of BPs.…”
Section: Dosing Of Btasmentioning
confidence: 99%
“…27,28 In a recent placebo controlled trial, denosumab significantly increased the bone-metastasis-free survival in patients with non-metastatic CRPC by a median of 4.2 months compared with placebo (29.5 vs. 25.2 months; HR, 0.85; 95% CI, 0.73-0.98; p = 0.028). 32 Denosumab is not approved for bone metastases prevention by Health Canada.…”
Section: Palliative Radiationmentioning
confidence: 99%